2023
DOI: 10.1038/s41398-023-02486-3
|View full text |Cite
|
Sign up to set email alerts
|

AKT and MAPK signaling pathways in hippocampus reveals the pathogenesis of depression in four stress-induced models

Abstract: Major depressive disorder (MDD) is a highly heterogeneous psychiatric disorder. The pathogenesis of MDD remained unclear, and it may be associated with exposure to different stressors. Most previous studies have focused on molecular changes in a single stress-induced depression model, which limited the identification of the pathogenesis of MDD. The depressive-like behaviors were induced by four well-validated stress models in rats, including chronic unpredictable mild stress, learned helplessness stress, chron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…A plethora of evidence suggests that PI3K-AKT signaling is a crucial pathway involved in the pathogenesis of depression ( Li et al, 2023 ). PI3K-Akt signaling regulates various neuronal activities such as synaptic neuroplasticity, cell proliferation, cell migration, and apoptosis ( Matsuda et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A plethora of evidence suggests that PI3K-AKT signaling is a crucial pathway involved in the pathogenesis of depression ( Li et al, 2023 ). PI3K-Akt signaling regulates various neuronal activities such as synaptic neuroplasticity, cell proliferation, cell migration, and apoptosis ( Matsuda et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Frontiers in Pharmacology frontiersin.org pathway, suggesting their critical role in the pathogenesis of depression. Among these pathways, the literature review showed a significant association between the PI3K-Akt signaling pathway (hsa04151) and MAPK signaling pathway (hsa04010) in the depression pathophysiology, suggesting targeting of these pathways by A. laxiflora's bioactive compounds as a possible mechanism of action (Su et al, 2017;Li et al, 2023). Notably, most of the PPI network's hub genes were involved in the PI3K-Akt signaling pathway (hsa04151), highlighting the importance of this pathway for identifying the underlying mechanism of A. laxiflora in depression in future exploratory studies.…”
Section: Go and Kegg Pathway Enrichment Analysismentioning
confidence: 99%
“…Furthermore, the MAPK and Ras signalling pathways were involved the target tiRNA-Gly-GCC-001 genes in KEGG analysis. Interestingly, the MAPK and Ras signalling pathways are modulated by stress and have been previously implicated in MDD and treatment response in human and animal models (Li, Teng, et al, 2023;Lopez et al, 2017) BDNF levels correlating with depression severity and recurrence (Greenberg et al, 2009;Park & Poo, 2013). BDNF also influences cell differentiation, migration and proliferation of cells (Monteiro et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Depression typically has a chronic course and significantly impairs individuals' capacity to work and their overall quality of life [ 1 ]. According to the World Health Organization (WHO), depression is anticipated to be the second most common cause of disease and disability by 2030, making it a major public health concern [ 2 ]. Over 300 million individuals worldwide suffer from depression, it is considered as one of the most frequent, costly and debilitating mental disorders [ 3 ].…”
Section: Introductionmentioning
confidence: 99%